2022
DOI: 10.1158/1535-7163.mct-21-0820
|View full text |Cite
|
Sign up to set email alerts
|

CD74-NRG1 Fusions Are Oncogenic In Vivo and Induce Therapeutically Tractable ERBB2:ERBB3 Heterodimerization

Abstract: NRG1 fusions are recurrent somatic genome alterations occurring across several tumor types, including invasive mucinous lung adenocarcinomas and pancreatic ductal adenocarcinomas and are potentially actionable genetic alterations in these cancers. We initially discovered CD74-NRG1 as the first NRG1 fusion in lung adenocarcinomas, and many additional fusion partners have since been identified. Here, we present the first CD74-NRG1 transgenic mouse model and provide evidence that ubiquitous expression of the CD74… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…24 Studies using CD74-NRG1 transgenic mouse models have shown that the proliferation of CD74-NRG1 cells is carcinogenic and accompanied by increased protein transcription levels of ERBB2 and ERBB3, indicating that NRG1 gene fusion drives tumor development. 25…”
Section: Fusion and Carcinogenic Mechanism Of Nrg1/2mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Studies using CD74-NRG1 transgenic mouse models have shown that the proliferation of CD74-NRG1 cells is carcinogenic and accompanied by increased protein transcription levels of ERBB2 and ERBB3, indicating that NRG1 gene fusion drives tumor development. 25…”
Section: Fusion and Carcinogenic Mechanism Of Nrg1/2mentioning
confidence: 99%
“… 24 Studies using CD74 - NRG1 transgenic mouse models have shown that the proliferation of CD74 - NRG1 cells is carcinogenic and accompanied by increased protein transcription levels of ERBB2 and ERBB3, indicating that NRG1 gene fusion drives tumor development. 25 NRG1 gene fusion is the first potential therapeutic oncogenic driver mutation specifically associated with a subtype of lung adenocarcinoma and is predominantly found in nonsmoking patients, in contrast to the tobacco-associated KRAS gene mutation. 24 In a transcriptome sequencing study of 25 never-smoking lung adenocarcinoma patients, one case of CD74 - NRG1 gene fusion was identified in a patient with invasive mucinous subtype.…”
Section: The Biological Basis Of the Nrg1/2 Genementioning
confidence: 99%
“…Neuregulin 1 ( NRG1 ) is a soluble ligand that ordinarily is released from cells and acts as a paracrine messenger [ 90 , 91 ]. NRG1 binds to HER3, promoting HER2/HER3 dimerization and PI3K/AKT/mTOR signaling [ 90 , 91 ]. NRG1 fusions are oncogenic drivers in PDAC and account for 1.3% of KRAS WT cases [ 63 , 92 ].…”
Section: Biomarker-driven Therapymentioning
confidence: 99%
“…NRG1 fusions are oncogenic drivers in PDAC and account for 1.3% of KRAS WT cases [ 63 , 92 ]. Mechanistically, NRG1 fusion proteins tether the NRG1 to the plasma membrane, resulting in hyperactivation of HER3 [ 90 , 91 ]. Zenocutuzumab, an investigational bispecific antibody targeting HER2 and HER3, has shown promising efficacy in patients with KRAS WT PDAC with NRG1 fusions [ 93 ].…”
Section: Biomarker-driven Therapymentioning
confidence: 99%
“…NRG1 is selectively expressed in the endocardium and myocardial microvessels. Recent research has revealed its intricate participation in various tumors, yielding molecular modifications across multiple tumor-associated signaling pathways ( 4 , 5 ). The intricate interplay between NRG1 and tumorigenesis has garnered substantial attention, particularly in the context of NSCLC.…”
Section: Introductionmentioning
confidence: 99%